Дослідження параметрів процесу формоутворення заготовок з порошкових матеріалів на вібропресовому обладнанні - Іскович-Лотоцький, Ростислав Дмитрович; Іванчук, Ярослав Володимирович; Івашко, Євгеній Іванович (НТУ "ХПІ", 2018)
На основі розробленої структури вібропресових формувальних машин, типів приводів та їх характеристик експериментально досліджено процес формоутворення заготовок з порошкових матеріалів вібраційним і віброударним способом обробки. Визначено збільшення середньої щільності заготовок відносно статичного пресування. За допомогою проведеного аналізу експериментальних даних якісних характеристик заготовок з порошкових матеріалів методом оцінки квантильного розмаху було обрано ефективні режими віброударного пресування, а також встановлена доцільність часового обмеження формування кінцевого виробу.

Determined high process efficiency of forming preforms from powder materials through vibration and vibro-impact processing. Based on the developed structure of vibropress molding machines, the types of drives and their characteristics, the process of shaping blanks from powder materials with a vibrating and vibro-impact processing method has been experimentally studied. The increase in the average density of blanks with respect to static pressing is determined. Through the analysis of the experimental data quality characteristics preforms from powder materials by quantile estimates amplitude were selected effective modes vibro compaction. The expediency of temporarily limiting the formation of the final product has been established. The development of a promising method for assessing the efficiency of technological processes for shaping blanks from powder materials, by developing a methodology for determining the basic parameters of the operation of vibropress equipment with a hydroimpulse drive, will increase the efficiency of its technological process.
Investigation of parameters of forming processing of bills from powder materials on vibrational pressing equipment
Keywords: вібропрес; експеримент; віброудар; пресування; vibropress; experiment; vibration pull